Hubungan antara Stres Akademik dan Dukungan Sosial Teman dengan Flow Akademik Mahasiswa - Anastasia Hanugrah Budiani; Lena Nessyana Pandjaitan; Listyo Yuwanto (Jurnal Ilmiah Psikologi MIND SET, 2021)
Academic flow occurs when someone can concentrate, enjoy and have internal motivation in academic activity. However, students often have difficulty experiencing flow, causing inability to appreciate their academic life. Therefore, through this study academic flow will be seen in relation to academic stress and social support from friends to see which variables could support academic flow. Data were collected from 176 students of the Faculty of Psychology whom were selected using haphazard sampling. The data were processed using non-parametric correlational analysis. The hypotheses in this study are academic stress correlates negatively and social support correlates positively with academic flow. The result is academic flow negatively correlated with academic stress -0.167 (p=0.013) while social support positively correlated 0.226 (p=0.001). Based on the result, it can be concluded that both hypotheses are accepted and social support from friends has a greater variable contribution (5.1%) than academic stress (2.8%) in supporting academic flow.